High-thermal-conductivity chip-level thermal interface material and preparation method thereof

By using silver powder as a thermal filler in chip-level thermal interface materials and using pressurized curing technology to form metal bond connections between nano silver powder and micro silver powder, the problem of insufficient thermal conductivity of existing materials is solved and the effect of high thermal conductivity is achieved , meet the heat dissipation needs of high-power chips.

CN119410156APending Publication Date: 2025-02-11SHENZHEN DARBOND INTERFACE MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411738727.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The thermal conductivity of existing chip-level thermal interface materials is insufficient and cannot meet the heat dissipation needs of high-power chips.

Method used

Silver powder is used as the thermal conductivity filler. By reasonably matching the ratio of micron silver powder and nano-silver powder, and using pressurized curing technology, the nano-silver powders are fused to each other and connected to micron silver powder to form metal bond connections, thereby reducing the thermal resistance in the thermal conductivity path.

Benefits of technology

It significantly improves the thermal conductivity of thermal interface materials, meets the heat dissipation needs of high-power chips, and solves the problem of low thermal conductivity of commercially available materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005162119390000071
    Figure BDA0005162119390000071
  • Figure HDA0005162119400000011
    Figure HDA0005162119400000011
Patent Text Reader

Abstract

The invention belongs to the technical field of chip-scale thermal interface materials and relates to a high-thermal-conductivity chip-scale thermal interface material and a preparation method thereof.The high-thermal-conductivity chip-scale thermal interface material comprises, by weight, 3-8 parts of double-terminated vinyl silicone oil and 0.5-2 parts of hydrogen-containing silicone oil; the composite material comprises the following components in parts by weight: 85-95 parts of a filling agent, 1-3 parts of a coupling agent, 0.01-0.1 part of an inhibitor and 0.01-0.1 part of a catalyst. The filler is composed of micron silver powder and nano silver powder in a weight ratio of (3-6): 1. Silver powder is used as heat-conducting filler, the proportion of micron silver powder to nano silver powder is reasonably matched, a pressurization curing process is adopted, the nano silver powder is fused with one another and connected with the micron silver powder, interaction between the filler is changed into metal key connection from physical contact, and therefore heat resistance in a heat-conducting channel is effectively reduced, and high heat conductivity is achieved; the heat dissipation requirement of a high-power chip is met, and the problem that a commercially available chip-level thermal interface material is low in heat conductivity is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chip-level thermal interface materials, and in particular relates to a high thermal conductivity chip-level thermal interface material and a preparation method thereof. Background Art

[0002] With the rise of 5G and AI technologies, the integration and power of chips such as GPUs and CPUs are increasing, and the demand for heat dissipation is increasing. Efficient heat dissipation is of great significance for improving the performance and reliability of chips. Chip-level thermal interface materials are mainly divided into two categories: traditional brazing thermal interface materials and emerging polymer-based thermal interface materials. Compared with brazing, polymer-based thermal interface materials have relatively simple processes and relatively low costs. However, the polymer-based thermal interface materials currently on the market mainly use alumina or aluminum powder as thermal conductive fillers, and form a thermal conductive path through physical contact between fillers. The thermal conductivity is mostly between 2-4W / mK, which cannot meet the heat dissipation needs of future high-power chips. Summary of the invention

[0003] In view of the deficiencies of the above-mentioned prior art, the present invention provides a high thermal conductivity chip-level thermal interface material and a preparation method thereof. The specific technical scheme is as follows:

[0004] The first object of the present invention is to provide a high thermal conductivity chip-level thermal interface material, comprising the following components in parts by weight:

[0005] 3-8 parts of double-terminated vinyl silicone oil, 0.5-2 parts of hydrogen-containing silicone oil; 85-95 parts of filler, 1-3 parts of coupling agent, 0.01-0.1 parts of inhibitor, 0.01-0.1 parts of catalyst;

[0006] The filler consists of micron silver powder and nano silver powder; the weight ratio of the micron silver powder to the nano silver powder is 3-6:1.

[0007] The high thermal conductivity chip-level thermal interface material of the present invention uses silver powder as a thermal conductive filler, and reasonably matches the ratio between micron silver powder and nano silver powder. If the weight ratio of the micron silver powder and the nano silver powder is higher than 6:1, the nano silver powder cannot fully contact the micron silver powder and cannot play a metal bond connection role; if the ratio is lower than 3:1, the content of the nano silver powder is too high, which will cause the viscosity of the system to be too high and cannot be dispensed smoothly.

[0008] Furthermore, the total molar ratio of the vinyl group in the double-terminated vinyl silicone oil to the silicon-hydrogen group in the hydrogen-containing silicone oil is 1:1-1.3, ensuring that the system has a suitable crosslinking degree.

[0009] Furthermore, the micron silver powder is spherical or nearly spherical in shape, and has a particle size of 1-20 μm, preferably 2-10 μm.

[0010] Furthermore, the preparation method of the nano silver powder is to dissolve polyvinyl pyrrolidone (PVP) in N,N-dimethylformamide (DMF) at 50-70° C. with stirring, and then drip silver nitrate solution into the above solution while stirring, and after the dripping is completed, stir the reaction for 1-3 hours and then centrifuge and dry to obtain the nano silver powder.

[0011] Furthermore, the particle size of the nano silver powder is 5-50 nm, preferably 10-30 nm.

[0012] The particle size of the nano silver powder used in the present invention should be less than 50 nm. If the particle size of the nano silver powder is greater than 50 nm, it cannot be melted when the thermal interface material is solidified.

[0013] Furthermore, the coupling agent is a silane coupling agent whose functional group is methoxy and whose main chain is polydimethylsiloxane.

[0014] Furthermore, the inhibitor is 1-butynyl cyclohexanol, the catalyst is an isopropanol solution of chloroplatinic acid with a mass fraction of 1%, and the platinum content is 10 ppm of the total weight of the catalyst.

[0015] The second object of the present invention is to provide a method for preparing the above-mentioned high thermal conductivity chip-level thermal interface material, comprising the following steps:

[0016] The double-terminated vinyl silicon, coupling agent and filler are stirred in vacuum at a speed of 15-30rpm and a temperature of 60-100°C for 60-120min, and the sides and bottom are scraped every 30min; then the material is cooled to room temperature, hydrogenated silicone oil and inhibitor are added, and the mixture is stirred in vacuum at a speed of 800-1200rpm for 2-5min, and then a catalyst is added and the mixture is stirred in vacuum at a speed of 800-1200rpm for 2-5min to obtain a uniform paste, and finally the paste is cured in an oven at 130-180°C under a pressure of 30-60psi for 20-40min to obtain a high thermal conductivity chip-level thermal interface material.

[0017] The high thermal conductivity chip-level thermal interface material of the present invention adopts a pressurized curing process. If a common curing process without applying external pressure during curing is adopted, it is not conducive to the mutual fusion of nano silver powders, and the thermal conductivity after curing is low or a longer curing time is required.

[0018] The beneficial effects of the present invention are:

[0019] The present invention uses silver powder as a thermal conductive filler to prepare a high thermal conductivity chip-level thermal interface material, optimizes the particle size of the silver powder, reasonably matches the ratio between micron silver powder and nano silver powder, and adopts a pressurized curing process, such as Figure 1As shown, during the curing process of the thermal interface material, the low-melting-point nano-silver powder will fuse with each other and connect the micron silver powder, so that the interaction between the fillers changes from physical contact to metal bond connection, thereby effectively reducing the thermal resistance in the heat conduction path, achieving high thermal conductivity, meeting the heat dissipation requirements of high-power chips, and solving the problem of low thermal conductivity of commercially available chip-level thermal interface materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram of the fusion and connection of nano silver powder and micron silver powder during the curing process of the thermal interface material of the present invention. DETAILED DESCRIPTION

[0021] The principles and features of the present invention are described below in conjunction with embodiments. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0022] The materials used in the examples and comparative examples of the present invention are as follows:

[0023] Double-terminated vinyl silicone oil: Zhejiang Runhe Silicone New Materials Co., Ltd., viscosity 500cST;

[0024] Hydrogenated silicone oil: Zhejiang Runhe Silicone New Materials Co., Ltd., viscosity 60cST;

[0025] Coupling agent: Shanghai Datian Chemical Co., Ltd., FM-0421.

[0026] Inhibitor: 1-butynylcyclohexanol;

[0027] Catalyst: 1% by mass chloroplatinic acid solution in isopropanol, with a platinum content of 10 ppm based on the total weight of the catalyst.

[0028] Preparation of nano silver powder by liquid phase reduction method:

[0029] By weight, 0.1 parts of PVP were dissolved in 100 parts of DMF at 60°C with stirring, and 15 parts of 0.02 mol / L silver nitrate solution were added dropwise to the above solution while stirring. After the addition was completed, the reaction was stirred for 2 hours and then centrifuged and dried to obtain nano silver powder (particle size 20 nanometers).

[0030] By weight, 0.05 parts of PVP were dissolved in 100 parts of DMF at 60°C under stirring, and 15 parts of 0.02 mol / L silver nitrate solution were added dropwise to the above solution while stirring. After the addition was completed, the mixture was stirred for reaction for 2 hours and then centrifuged and dried to obtain nano silver powder (particle size 80 nanometers).

[0031] Embodiment 1:

[0032] Preparation of a high thermal conductivity chip-level thermal interface material:

[0033] According to weight, 6.3 parts of double-terminated vinyl silicone oil, 2 parts of coupling agent, 90 parts of filler (the mass ratio of micron silver powder with a particle size of 5 microns and nano silver powder with a particle size of 20 nanometers is 4:1), the speed is 20rpm, the temperature is 80℃, and the vacuum stirring is 90min, and the edges and bottoms are scraped once every 30min; then the materials are cooled to room temperature and put into a stirring tank, 1.6 parts of hydrogenated silicone oil (the ratio of silicon hydrogen to vinyl content in the system is 1.2:1), 0.05 parts of inhibitor are added, and the speed is 1000rpm in a planetary high-speed mixer. The speed is vacuum stirred for 3min, and then 0.05 parts of catalyst are added, and the speed is vacuum stirred for 3min at 1000rpm to obtain a uniform paste. The curing process of the paste is to apply 50psi pressure in a 150℃ oven for 30min.

[0034] Example 2

[0035] Preparation of a high thermal conductivity chip-level thermal interface material:

[0036] According to weight, 5 parts of double-terminated vinyl silicone oil, 1.6 parts of coupling agent, 92 parts of filler (the mass ratio of micron silver powder with a particle size of 5 microns and nano silver powder with a particle size of 20 nanometers is 4:1), the speed is 20rpm, the temperature is 80℃, and the vacuum stirring is 90min, and the edges and bottoms are scraped once every 30min; then the materials are cooled to room temperature and put into a stirring tank, 1.3 parts of hydrogenated silicone oil (the ratio of silicon hydrogen to vinyl content in the system is 1.2:1), 0.05 parts of inhibitor are added, and the speed of 1000rpm is vacuum stirred for 3min in a planetary high-speed mixer, and then 0.05 parts of catalyst are added, and the speed of 1000rpm is continued to be vacuum stirred for 3min to obtain a uniform paste. The curing process of the paste is to apply 50psi pressure in a 150℃ oven for 30min.

[0037] Comparative Example 1

[0038] Preparation of a chip-level thermal interface material:

[0039] According to weight, 5 parts of double-terminated vinyl silicone oil, 1.6 parts of coupling agent, 92 parts of filler (the mass ratio of micron silver powder with a particle size of 5 microns and nano silver powder with a particle size of 80 nanometers is 4:1), the speed is 20rpm, the temperature is 80℃, and the vacuum stirring is 90min, and the edges and bottoms are scraped once every 30min; then the materials are cooled to room temperature and put into a stirring tank, 1.3 parts of hydrogenated silicone oil (the ratio of silicon hydrogen to vinyl content in the system is 1.2:1), 0.05 parts of inhibitor are added, and the speed of 1000rpm is vacuum stirred for 3min in a planetary high-speed mixer, and then 0.05 parts of catalyst are added, and the speed of 1000rpm is continued to be vacuum stirred for 3min to obtain a uniform paste. The curing process of the paste is to apply 50psi pressure in a 150℃ oven for 30min.

[0040] Comparative Example 2

[0041] Preparation of a chip-level thermal interface material:

[0042] According to weight, 5 parts of double-terminated vinyl silicone oil, 1.6 parts of coupling agent, 92 parts of filler (the mass ratio of micron silver powder with a particle size of 5 microns and nano silver powder with a particle size of 20 nanometers is 8:1), the speed is 20rpm, the temperature is 80℃, and the vacuum stirring is 90min, and the edges and bottoms are scraped once every 30min; then the materials are cooled to room temperature and put into a stirring tank, 1.3 parts of hydrogenated silicone oil (the ratio of silicon hydrogen to vinyl content in the system is 1.2:1), 0.05 parts of inhibitor are added, and the speed of 1000rpm is vacuum stirred for 3min in a planetary high-speed mixer, and then 0.05 parts of catalyst are added, and the speed of 1000rpm is continued to be vacuum stirred for 3min to obtain a uniform paste. The curing process of the paste is to apply 50psi pressure in a 150℃ oven for 30min.

[0043] Comparative Example 3

[0044] Preparation of a chip-level thermal interface material:

[0045] According to weight, 5 parts of double-terminated vinyl silicone oil, 1.6 parts of coupling agent, 92 parts of filler (the mass ratio of micron silver powder with a particle size of 5 microns and nano silver powder with a particle size of 20 nanometers is 2:1), the speed is 20rpm, the temperature is 80℃, and the vacuum stirring is 90min, and the edges and bottoms are scraped once every 30min; then the materials are cooled to room temperature and put into a stirring tank, 1.3 parts of hydrogen-containing silicone oil (the ratio of silicon hydrogen to vinyl content in the system is 1.2:1), 0.05 parts of inhibitor are added, and the vacuum speed is 1000rpm in a planetary high-speed mixer for 3min, and then 0.05 parts of catalyst are added, and the vacuum stirring is continued at a speed of 1000rpm for 3min to obtain a uniform paste. The curing process of the paste is to apply 50psi pressure in a 150℃ oven for 30min.

[0046] Comparative Example 4

[0047] Preparation of a chip-level thermal interface material:

[0048] According to weight, 6.3 parts of double-terminated vinyl silicone oil, 2 parts of coupling agent, 90 parts of filler (the mass ratio of micron silver powder with a particle size of 5 microns and nano silver powder with a particle size of 20 nanometers is 4:1), the speed is 20rpm, the temperature is 80℃, and the vacuum stirring is 90min, and the edges and bottoms are scraped once every 30min; then the materials are cooled to room temperature and put into a stirring tank, 1.6 parts of hydrogenated silicone oil (the ratio of silicon hydrogen group to vinyl content in the system is 1.2:1), 0.05 parts of inhibitor are added, and the speed of 1000rpm is vacuum stirred for 3min in a planetary high-speed mixer, and then 0.05 parts of catalyst are added, and the speed of 1000rpm is continued to be vacuum stirred for 3min to obtain a uniform paste. The curing process of the paste is to keep warm in an oven at 150℃ for 30min (without applying external pressure).

[0049] Comparative Example 5

[0050] Preparation of a chip-level thermal interface material:

[0051] According to weight, 6.3 parts of double-terminated vinyl silicone oil, 2 parts of coupling agent, 90 parts of filler (the mass ratio of micron silver powder with a particle size of 5 microns and nano silver powder with a particle size of 20 nanometers is 4:1), the speed is 20rpm, the temperature is 80℃, and the vacuum stirring is 90min, and the edges and bottoms are scraped once every 30min; then the materials are cooled to room temperature and put into a stirring tank, 1.6 parts of hydrogenated silicone oil (the ratio of silicon hydrogen to vinyl content in the system is 1.2:1), 0.05 parts of inhibitor are added, and the speed of 1000rpm is vacuum stirred for 3min in a planetary high-speed mixer, and then 0.05 parts of catalyst are added, and the speed of 1000rpm is continued to be vacuum stirred for 3min to obtain a uniform paste. The curing process of the paste is to keep warm in an oven at 150℃ for 2h (without applying external pressure).

[0052] Table 1 shows the basic performance test results of chip-level thermal interface materials prepared in Examples 1-2 and Comparative Examples 1-5, wherein the viscosity of the paste is tested using a Haake rheometer, a needle with an inner diameter of 0.7 mm and an air pressure of 80 psi are used for dispensing, and the thermal conductivity of the paste before curing and the product after curing is tested using a hot disk.

[0053] Table 1 Basic performance test results

[0054]

[0055] The basic performance test results in Table 1 show that the pastes obtained in Examples 1-2 are all dispensed smoothly, and the thermal conductivity is more than doubled after curing compared with before curing. However, the particle size of the nano-silver powder in Comparative Example 1 is relatively high, and it is difficult to melt at a curing temperature of 150°C, resulting in physical contact between the silver powders after curing, and the thermal conductivity is not significantly improved. The content of nano-silver powder in Comparative Example 2 is too low, and the micron silver powder cannot be effectively connected by metal bonds during the curing process, and the thermal conductivity is not significantly improved. The content of nano-silver powder in Comparative Example 3 is too high, and the viscosity of the paste is too high to be dispensed; in addition, although the thermal conductivity is significantly improved after curing, the improvement efficiency is lower than that of Examples 1-2. In Comparative Example 4, a conventional curing process (without applying external force) is adopted. During the 30-minute insulation time, the mutual fusion between the nano-silver powders in the system is insufficient, and the thermal conductivity after curing is significantly lower than that of Example 1. Comparative Example 5 also adopts a conventional curing process (without applying external force), but increases the holding time to 2 hours. The increase in the holding time is beneficial to improving the mutual fusion between the nano-silver powders. The thermal conductivity after curing is significantly higher than that of Comparative Example 4 which is only kept warm for 30 minutes, but is still lower than that of Example 1 which adopts a pressurized curing process.

[0056] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A high thermal conductivity chip-level thermal interface material, characterized in that: The composition comprises the following components in parts by weight: 3-8 parts of double-terminated vinyl silicone oil, 0.5-2 parts of hydrogen-containing silicone oil; 85-95 parts of filler, 1-3 parts of coupling agent, 0.01-0.1 parts of inhibitor, 0.01-0.1 parts of catalyst; The filler is composed of micron silver powder and nano silver powder; the weight ratio of the micron silver powder to the nano silver powder is 3-6:

1.

2. The high thermal conductivity chip-level thermal interface material according to claim 1, characterized in that: The total molar ratio of the vinyl groups in the double-terminated vinyl silicone oil to the silicon-hydrogen groups in the hydrogen-containing silicone oil is 1:1-1.

3.

3. The high thermal conductivity chip-level thermal interface material according to claim 1, characterized in that: The preparation method of the nano silver powder comprises the following steps: dissolving polyvinyl pyrrolidone in N,N-dimethylformamide at 50-70° C. by stirring, then dripping a silver nitrate solution into the solution while stirring, stirring for reaction for 1-3 hours after the dripping is completed, and then centrifugally drying to obtain the nano silver powder.

4. The high thermal conductivity chip-level thermal interface material according to claim 1, characterized in that: The particle size of the micron silver powder is 1-20 μm.

5. The high thermal conductivity chip-level thermal interface material according to claim 3, characterized in that: The particle size of the nano silver powder is 5-50nm.

6. The high thermal conductivity chip-level thermal interface material according to claim 1, characterized in that: The coupling agent is a silane coupling agent whose functional group is methoxy and whose main chain is polydimethylsiloxane.

7. The high thermal conductivity chip-level thermal interface material according to claim 1, characterized in that: The inhibitor is 1-butynylcyclohexanol.

8. The high thermal conductivity chip-level thermal interface material according to claim 1, characterized in that: The catalyst is an isopropanol solution of chloroplatinic acid with a mass fraction of 1%.

9. The high thermal conductivity chip-level thermal interface material according to claim 5, characterized in that: The particle size of the micron silver powder is 2-10 μm; the particle size of the nano silver powder is 10-30 nm.

10. A method for preparing a high thermal conductivity chip-level thermal interface material according to any one of claims 1 to 9, characterized in that: The steps include: The double-terminated vinyl silicon, coupling agent and filler are stirred under vacuum at a speed of 15-30rpm and a temperature of 60-100°C for 60-120min, and the sides and bottom are scraped every 30min; then the material is cooled to room temperature, hydrogenated silicone oil and inhibitor are added, and the mixture is stirred under vacuum at a speed of 800-1200rpm for 2-5min, and then a catalyst is added, and the mixture is stirred under vacuum at a speed of 800-1200rpm for 2-5min to obtain a uniform paste, and finally the paste is cured in an oven at 130-180°C under a pressure of 30-60psi for 20-40min to obtain a high thermal conductivity chip-level thermal interface material.